Antibacterial activity of Kombucha against Escherichia coli and Staphylococcus aureus and Minas Frescal cheese production with Scoby (Research, Society and Development, 2022)
Functional ingredients have become common in food products. The fermented Kombucha drink stands out for its probiotic and antimicrobial properties that beneficially contribute to food use. The present study aimed at assessing the antimicrobial activity of Kombucha in experimentally contaminated cheeses. Therefore, Minas Frescal cheeses were prepared, inoculated with Escherichia coli and divided into three treatments:  1) lactic acid bacteria (BioRich®); 2) lactic bacteria (BioRich ®) and 10 g of Scoby (symbiotic culture of bacteria and yeasts); 3) 10 g of Scoby. The gelatinous film (Scoby) was used to produce the Kombucha extract. The experimental design was a 3 x 4 factorial arrangement with three treatments and four evaluation times. Data was analyzed with ANOVA, and treatments means were compared with the Tukey test (p £ 0.05). The parameters of minimum inhibitory concentration, color, texture, pH, acidity, water activity, counting of yeasts, lactobacilli, and total coliforms were evaluated on days 0, 3, 6, and 9 of storage. Antibacterial action of Kombucha was compared against Escherichia coli and Staphylococcus aureus bacteria for minimum inhibitory concentration. Acidity, bacterial counting, yeasts, coliforms, lactobacilli, hardness, and gumminess showed significant changes with the addition of Kombucha to cheeses (p £ 0.05). However, However, the addition of Kombucha to the cheeses did not reduce the coliform content and negatively altered the texture parameters.